Correction: Composite sodium metal anodes for practical applications. Issue 31 (2nd July 2020) - Cui, Jiayu; Wang, Aoxuan; Li, Guojie; Wang, Donghong; Shu, Da; Dong, Anping; Zhu, Guoliang; Luo, Jiayan; Sun, Baode
Abstract : Correction for 'Composite sodium metal anodes for practical applications' by Jiayu Cui et al., J. Mater. Chem. A, 2020, DOI: ; 10.1039/d0ta02469d .